Carmen Rabell. Rewriting the Italian novella in counter-reformation Spain. Tamesis, London, 2003; 172 pp. - López Martínez, José Enrique (El Colegio de México, 2006)
Se reseñó el libro: Rewriting the Italian novella in counter-reformation Spain.